Simulation of the effect of regenerator porosity on the performance of zero centrigade thermoacoustic cooler generated by the single-stage thermoacoustic machine for sustainable refrigeration - Farikhah, Irna; Aldiansyah, Edo Putra; Khoiri, Nur; Ristanto, Sigit; Wibowo, Setyoningsih (Widya Teknik, 2024)
Refrigeration systems are an essential need in everyday life. There are lots of modern industry that uses refrigerator for helps maintain temperature stability from overheating and prevents the product from drying out protected from dirt and insect attacks. However, the refrigeration system used in industry still uses a refrigeration system vapor compression and using chlorofluorocarbon (CFC) refrigerant and hydro-chlorofluorocarbons (HCFCs) which are harmful to the environment. Therefore, it requires thermoacoustic cooling generated by the engine single-stage thermoacoustic. This research was conducted numerically. In this research, the effects are simulated stack porosity on the performance of thermoacoustic cooling generated by a single-stage thermoacoustic machine at 0°C. the porosity was varied from 0.37 to 0.97. It was found that the stack porosity was optimal when the porosity is 0.97 and the performance of the cooler is 52 %. Moreover, the lowest heating temperature for the thermoacoustic machine is 217°C. This temperature can be used for waste heat recovery.